Fish Bioacoustics - Webb, Jacqueline F.; Fay, Richard R.; Popper, Arthur N. (Springer Handbook of Auditory Research,, 2008)
The study of how fish make and respond to sound has important implications for communication, physiology, behavior, and commercial techniques. Fish Bioacoustics, a new definitive volume on fish auditory systems, will interest investigators in both basic research of fish bioacoustics as well as investigators in applied aspects of fisheries and resource management. Topics cover structure, physiology, localization, and acoustic behavior as well as more applied topics such as using sound to detect and locate fish. Contents: Introduction to Fish Bioacoustics Richard R. Fay, Arthur N. Popper, and Jacqueline F. Webb Hearing and Acoustic Behavior (Basic and Applied) Arthur N. Popper and Carl R. Schilt Structures and Functions of the Auditory Nervous System of Fishes Richard R. Fay and Peggy L. Edds-Walton Evolution of Peripheral Mechanisms for the Enhancement of Sound Reception Christopher B. Braun and Terry Grande Bioacoustics and the Lateral Line of Fishes Jacqueline F. Webb, John Montgomery, and Joachim Mogdans Orientation to Auditory and Lateral Line Stimuli Olav Sand and Horst Bleckmann Multipole Mechanisms for Directional Hearing in Fish Peter H. Rogers and David G. Zeddies Vocal-Acoustic Communication: From Neurons to Behavior Andrew H. Bass and Friedrich Ladich Active and Passive Acoustics to Locate and Study Fish David A. Mann, Anthony D. Hawkins, and J. Mike Jech About the editors: Jacqueline F. Webb is Professor of Biological Sciences, and Coordinator of the Marine Biology Program, at the University of Rhode Island, Kingston. Richard R. Fay is Director of the Parmly Hearing Institute and Professor of Psychology at Loyola University of Chicago. Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. About the series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.